The role of midwife nurses and nursing students in antibiotic stewardship for maternal and child health: an evidence-based systematic review - Brown, Anna E.; Bahl, Heena; Usha, Chakali; Umar, Mohammed; Bhadauriya, Shiva; Mary T., Beaulah Mercy; Pritika; Rohit; Mandal, Tanusri (International Journal Of Community Medicine And Public Health, 2025)
Antimicrobial resistance (AMR) poses a critical global health challenge, particularly within maternal and child health (MCH) settings where inappropriate antibiotic use heightens infection risks, maternal morbidity, and neonatal complications. Strengthening antibiotic stewardship programs (ASPs) in MCH services is therefore essential to preserve antimicrobial effectiveness and improve clinical outcomes. This review examined the multifaceted roles of midwife nurses and nursing students in advancing antimicrobial stewardship, focusing on educational readiness, clinical participation, and policy engagement. Using PRISMA 2020 guidelines, a comprehensive search of PubMed, CINAHL, Scopus, and Web of Science (2013–2025) identified eligible studies. Evidence was screened using PICO criteria and appraised through Joanna Briggs Institute (JBI) and mixed methods appraisal tool (MMAT) frameworks. Forty-two studies, including randomized controlled trials, quasi-experimental designs, cross-sectional surveys, and qualitative analyses, were narratively and thematically synthesized across domains of clinical practice, education, infection prevention, and policy integration. Findings demonstrated improved adherence to stewardship guidelines (25–40%), significant reductions in antibiotic overuse (30–50%), and notable gains in knowledge and IPC competencies (+30–45%) following nurse-led and student-centered interventions. Educational innovations such as simulation-based learning, stewardship modules, and midwife-driven ASP models were particularly effective in promoting rational antibiotic use. Despite strong evidence supporting their contributions, challenges persist, including limited policy recognition, variable training structures, and disparities across low- and middle-income countries. Strengthening AMS education, integrating stewardship into routine MCH practice, and ensuring formal policy inclusion of midwives and nursing students are imperative to advance antimicrobial optimization and safeguard maternal–neonatal health globally.